2016
DOI: 10.1080/10286020.2016.1201811
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of liquiritin on cognitive deficits induced by soluble amyloid-β1–42 oligomers injected into the hippocampus

Abstract: This study assessed the modulating effects of liquiritin against cognitive deficits, oxidative damage, and neuronal apoptosis induced by subsequent bilateral intrahippocampal injections of aggregated amyloid-β (Aβ). This study also explored the molecular mechanisms underlying the above phenomena. Liquiritin was orally administered to rats with Aβ-induced cognitive deficits for 2 weeks. The protective effects of liquiritin on the learning and memory impairment induced by Aβ were examined in vivo by using Morris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Many of these components are associated with cognition. Hydroxymethylfurfural is a potential therapeutic agent for AD [ 41 ]; liquiritin and ferulic acid are useful for amelioration of amyloid β peptide-induced cognitive impairment [ 42 , 43 ]; paeoniflorin reverses the muscarinic receptor-mediated inhibition of long-term potentiation [ 44 ]; nodakenin enhances adult hippocampal neurogenesis [ 45 ], ginsenoside Rg1 delays cognitive decline and promotes neurogenesis [ 46 , 47 ], and glycyrrhizin ameliorates cognitive decline via anti-inflammatory effects [ 48 ]. Further studies of the efficacy and underlying mechanism of these Palmultang constituents should continue to elucidate their effects on cognitive dysfunction comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these components are associated with cognition. Hydroxymethylfurfural is a potential therapeutic agent for AD [ 41 ]; liquiritin and ferulic acid are useful for amelioration of amyloid β peptide-induced cognitive impairment [ 42 , 43 ]; paeoniflorin reverses the muscarinic receptor-mediated inhibition of long-term potentiation [ 44 ]; nodakenin enhances adult hippocampal neurogenesis [ 45 ], ginsenoside Rg1 delays cognitive decline and promotes neurogenesis [ 46 , 47 ], and glycyrrhizin ameliorates cognitive decline via anti-inflammatory effects [ 48 ]. Further studies of the efficacy and underlying mechanism of these Palmultang constituents should continue to elucidate their effects on cognitive dysfunction comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that liquiritin is beneficial in the treatment of neurodegenerative diseases such as AD [102]. Treating cells with liquiritin along with low doses of NGF aids in the enhancement of neurite outgrowth probably by increasing the expression levels of important neuronal related genes such as Neurog 3, Nf 1, Notch 2, Nmur 2 and Ntf 5, ultimately leading to neural regeneration, differentiation and synapse formation [103].…”
Section: Miscellaneous Tcm Active Molecules Showing Neurogenic Potmentioning
confidence: 99%
“…Three bioactive components in TWBXP, liquiritin, deoxyschizandrin, and tanshinone II A, have been proven to be closely related to the therapy effect of neurodegenerative disease. Liquiritin is a major ingredient in Glycyrrhizae radix which has been proven to significantly ameliorate spatial learning, cognitive ability, and memory impairment of rats with Alzheimer's disease [9]. It possessed various pharmacological activities and exhibited various positive biological effects, including neuroprotective [10], anticancer [11], and antidepressant [12] effect.…”
Section: Introductionmentioning
confidence: 99%